Analisis Unsur Budaya Jawa Wayang pada Cerpen Semar Tresno - Aisyah Novy Prabawati; Imam Baihaqi (KABASTRA: Kajian Bahasa dan Sastra, 2026)
Culture is all the results of the work, creativity, and feelings of society so that all forms of a community group are forms of culture which then in one society creates many cultural aspects. Based on the elements that form the culture, this article will discuss art which is part of culture and a means used to express the sense of beauty from within the human soul and has other functions. The descriptive qualitative analytical approach method is a method used to obtain in-depth data, data that contains meaning and can significantly influence the substance of the research. In the short story entitled "Semar tresno" teaches us simple things in life, for example the character Semar who is grateful for the blessings that God has given in the morning when the sun begins to rise from its bed along with the garden birds leaving their nests. Wayang can be interpreted as a puppet to imitate people made of broken leather or wood and used to present characters in a traditional drama performance created according to the character, nature, and behavior of a character. Gareng and Petruk have contrasting characters. Wayang can be defined as a puppet made from broken leather or wood to imitate humans and used to portray characters in traditional drama performances, created to reflect the character's character, traits, and behavior. The puppets studied in this article are short stories that take on names or roles such as Punokawan, represented by Semar, Gareng, Petruk, and Bagong.